2017
DOI: 10.1007/s00203-017-1386-x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of anti-biofilm and anti-virulence properties of dihydrocelastrol and dihydrocelastryl diacetate in fighting against methicillin-resistant Staphylococcus aureus

Abstract: Human pathogens have readily been converted into multidrug-resistant pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA), because of the long-term use of conventional antibiotics. In addition, the biofilms formed by S. aureus cells are especially problematic and are related to the persistence of chronic infections because they constitute a major mechanism of promoting tolerance to diverse antimicrobial agents. Hence, the inhibitions of biofilm formation and/or toxin production are accepted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…There are many possible mechanisms of the killing action by the extract such as anti-quorum sensing, surface modification mechanism and disruption of crucial genes. For instance, Woo et al ( 38 ) reported the effectiveness of antibiofilm activity of the bioactive compounds, dihydrocelastrol and dihydrocelastryl diacetate. They revealed that both these bioactive compounds were able to down-regulated the expression of crucial genes for biofilm formation, such as RNAIII in MRSA, and disturb the gene expression related to α-hemolysin.…”
Section: Discussionmentioning
confidence: 99%
“…There are many possible mechanisms of the killing action by the extract such as anti-quorum sensing, surface modification mechanism and disruption of crucial genes. For instance, Woo et al ( 38 ) reported the effectiveness of antibiofilm activity of the bioactive compounds, dihydrocelastrol and dihydrocelastryl diacetate. They revealed that both these bioactive compounds were able to down-regulated the expression of crucial genes for biofilm formation, such as RNAIII in MRSA, and disturb the gene expression related to α-hemolysin.…”
Section: Discussionmentioning
confidence: 99%
“…The colored solution was measured at wavelength 545 nm. The readings were used to calculate the biofilm formation index ( Kwasny and Opperman, 2010 ; Coffey and Anderson, 2014 ; Woo et al., 2017 ; Jang et al., 2020 ). Five technical replicates were used for each bacterial strain to compensate for variability and three biological replicates were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm inhibition assay was performed in 96-well polystyrene plates (BD, Falcon) as previously described (Deziel et al 2001;Woo et al 2017a) with minor modifications. Briefly, bacterial cell suspensions were inoculated into LB medium (total volume 200 ll) containing different concentrations of auranofin (4-48 lg ml À1 ) and incubated at 37°C for 24 h under 5% CO 2 condition.…”
Section: Crystal-violet Biofilm Assaymentioning
confidence: 99%
“…Biofilm eradication concentration (BEC) assay was performed to confirm the ability of auranofin to remove preformed biofilm. BEC assay was performed in 96-well polystyrene plates (BD, Falcon) as previously described (Nostro et al 2007;Woo et al 2017a) with some modifications. Briefly, bacterial cell suspension at a concentration of 1 9 10 6 CFU per ml without auranofin treatment was incubated at 37°C for 24 h under 5% CO 2 condition.…”
Section: Biofilm Eradication Concentration Assaymentioning
confidence: 99%